1992
DOI: 10.1177/019459989210600127
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model of Chronic Tympanic Membrane Perforation

Abstract: Previous investigations into the healing and reconstruction of tympanic membrane (TM) perforations have involved animal models with acute TM perforations. A problem with the acute TM perforation model is that most acute TM perforations will heal spontaneously, both in animals and human beings. A second inadequacy of acute perforation models is that they are not analogous to the salient problem in human beings: long-standing TM perforation. The ideal animal model must have a TM perforation that is permanent, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 15 publications
(3 reference statements)
2
65
1
2
Order By: Relevance
“…Laidlaw et al [17] applied re-myringotomy in chinchillas and reported chronic TMP in 85% of animals after a period of five to eight weeks. Numerous studies have evaluated re-myringotomy technique in combination with thermal injury and/or infolding technique showing variable success rates ranging from 69-100% [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Laidlaw et al [17] applied re-myringotomy in chinchillas and reported chronic TMP in 85% of animals after a period of five to eight weeks. Numerous studies have evaluated re-myringotomy technique in combination with thermal injury and/or infolding technique showing variable success rates ranging from 69-100% [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Histologicamente, a membrana timpânica apresenta 3 camadas: uma camada epitelial, composta por duas fileiras de células epiteliais; uma intermediária fina de constituição fibrosa, com fibras de natureza colágena, fibroblastos e células endoteliais e uma média de natureza mucosa, que se continua com a mucosa do ouvido médio [3][4][5][6][7] .…”
Section: Introductionunclassified
“…Meerschweinchen und Chinchillas vor[1,6,26,31,32].Da die Trommelfellreparation bei diesen Tieren schnell und hartnäckig erfolgt, spricht man bei Persistenz des Defektes über 5-8 Wochen von chronischen Perforationen [1, 22, 31]. Wir haben im vorliegenden Versuch einen Zeitraum von 8 Wochen gewählt und die Ratte aufgrund einer dem Menschen ähnlichen Trommelfellstruktur [28] sowie aus Preisgründen bevorzugt.…”
unclassified